Definition and quantification of behaviour coefficients based on structural reliability concepts. - Duarte, R.T. (2017)
A methodology for the definition and quantification of behaviour coefficients to be used in the earthquake design of structure is presented. These coefficients are defined for specific design methods and are quantified by a target value of the probability of collapse. The methodology is quantified through the analysis and safety checking of structures defined by single variable models.